3D numerical study on the influence of particle porosity on heat and fluid flow. (26th June 2012) - Wittig, Kay; Golia, Aakash; Nikrityuk, Petr A.
This work is devoted to the three–dimensional numerical simulations of the heat and fluid flow past and through a porous spherical particle over a wide range of Reynolds numbers (20 < Re < 500) corresponding to the steady–state flow and different values of porosity varying between 0.62 and 0.92. The porosity of a particle is modelled using two approaches corresponding to a microscopic and macroscopic representation of the pores, respectively. Specifically, in the first approach the porous particle is represented by a cluster of small spherical particles distributed inside the porous particle. The second approach represents the porosity implicitly utilising the so–called permeability model, adopting the Blake–Kozeny equation to treat the fluid and heat flow inside a particle. The comparison of the two models showed good agreement for a porosity below 0.7. The analysis of numerical simulations showed that for a constant Reynolds number (Re < 100), with increasing porosity, the value of the drag coefficient decreases slightly. However, when the Reynolds number is increased (Re > 100) a local maximum in the drag force coefficient was observed for a porosity of about 0.76. On the basis of the results of simulations, expressions are derived and examined for the drag coefficient and the surface–averaged Nusselt number.